Analisis Penerapan Risiko Operasional Dan Kepatuhan Syariah Badan Wakaf Al-Qur’an Ditinjau Dari Waqf Core Principles - Sakum; Neng Wiwi; MH Ainulyaqin; Sarwo Edy; Listian Indriyani Achmad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
ABSTRACT. Operational Risk and Sharia Compliance are indicators contained in the waqf Core Principles, which have been applied by the Bekasi Branch Al-Qur’an Waqf Board in minimising operational risks that will occur and indications of sharia compliance. The Waqf assets issued by the Al-Qur’an Waqf Board to the public are Al-Qur’an mushaf, where the waqif donates by giving a sum of money will be used for all operational purposes from collecting money, printing, storing and distributing Al-Qur’an throughout the country. This study aims to analyse the application of Operational Risk and analyse of Sharia Compliance at the Bekasi Branch of the Al-Qur’an Waqf Board. This method with descriptive research and field research. Data collection is carried out by observation and interview process. The results showed that: From six indicators of Operational Risk and from ten indicators of Sharia Compliance, the Al-Qur’an Waqf Board has implemented all of them based on the Waqf Core Principles.